Design of a Matlab toolbox and GUI for minimal realizations - Karim Cherifi; Kamel Hariche (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
Minimal realization for linear systems has been studied extensively in the literature. Techniques proposed differ in terms of the configuration of the state space form, the time efficiency of the algorithm and the reduction of memory storage. The minimal realization toolbox presented in this paper offers the possibility to test different methods and choose the most suitable form depending on the application. The given system can be represented by a transfer function or by raw (frequency or time domain) data. A graphical user interface (GUI) was implemented in order to ease the use of this toolbox and allow to rapidly test the methods and display the results.